Kajian Penataan Massa Terhadap Aksesibilitas Pengguna Jakabaring Sport City - Chairul Nas, Serdian; Winarto, Erwin Djuni (Universitas Medan Area, 2025)
Jakabaring Sport City (JSC), or the Jakabaring Sports Complex, is one of the largest sports complexes in Indonesia, located in Palembang City. JSC is equipped with a comprehensive range of facilities, both for sports and non-sports activities. These facilities are spread across an area of 325 hectares, with the Gelora Sriwijaya Stadium serving as the central focus of the mass arrangement. As a public building, JSC is frequently visited, especially during events held at the complex. Therefore, this study aims to assess the effectiveness of the mass arrangement in relation to user accessibility. The research employs a qualitative method through literature review. Data collection techniques involve searching for data, conducting research, and drawing conclusions. The study findings indicate that the mass arrangement at JSC also considers user activities, which affects accessibility and circulation. The mass arrangement at JSC is deemed sufficiently efficient for the various activities carried out by its users.